2014
DOI: 10.1097/dcr.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Elastic Laminal Invasion in Colon Cancer

Abstract: Elastic laminal invasion adversely influences prognosis in pT3 and pT4a colon cancer. Although elastic laminal invasion positivity does not affect prognosis in node-positive patients receiving adjuvant chemotherapy, node-negative patients with elastic laminal invasion have a similar risk of recurrence as node-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…Embedded within the connective tissue, the peritoneal elastic lamina (PEL) has been identified [2,3]. In patients with colon carcinoma, tumor invasion with an intact PEL has been associated with increased survival compared to tumor invasion with a fragmented PEL [4,5]. However, for peritoneal metastases of EOC, the prognostic relevance of the PEL and their correlation with depth of metastatic tumor invasion is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Embedded within the connective tissue, the peritoneal elastic lamina (PEL) has been identified [2,3]. In patients with colon carcinoma, tumor invasion with an intact PEL has been associated with increased survival compared to tumor invasion with a fragmented PEL [4,5]. However, for peritoneal metastases of EOC, the prognostic relevance of the PEL and their correlation with depth of metastatic tumor invasion is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…ET stains can also highlight the peritoneal elastic lamina which provides a useful landmark when the serosa is obscured by a desmoplastic or fibro-inflammatory reaction; moreover, there is emerging evidence that penetration beyond the peritoneal elastic lamina may be associated with adverse outcomes in pT3 CRC. [35][36][37][38][39] Four pathologists indicated that PNI was easier to evaluate on ET than H&E, possibly due to the improved contrast between the nerves (dusty light green-blue) and muscularis propria (brown-red), whereas only 2/10 observers found PNI easier to evaluate on H&E (4 reported no difference between the 2 stains). Nonetheless, neither accuracy nor reproducibility of pT stage or PNI differed between H&E and ET sections.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 8 of 10 observers considered the ease of assessment of T-stage to be at least equivalent on ET compared with H&E, with 4 considering ET to be the superior stain for this assessment. ET stains can also highlight the peritoneal elastic lamina which provides a useful landmark when the serosa is obscured by a desmoplastic or fibro-inflammatory reaction; moreover, there is emerging evidence that penetration beyond the peritoneal elastic lamina may be associated with adverse outcomes in pT3 CRC 35–39. Four pathologists indicated that PNI was easier to evaluate on ET than H&E, possibly due to the improved contrast between the nerves (dusty light green-blue) and muscularis propria (brown-red), whereas only 2/10 observers found PNI easier to evaluate on H&E (4 reported no difference between the 2 stains).…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal elastic lamina, located immediately beneath the basement membrane of mesothelial cells, can be a landmark for assessing tumor spread in colon cancer. Peritoneal elastic laminal invasion (ELI) detected using elastic staining can reportedly be a prognostic factor in pT3 and pT4a colon cancer and can be introduced in pT classification, similar to that in lung cancer 11–20 . Furthermore, various studies have presented several arguments regarding the introduction of elastic staining in routine pathologic practice, in terms of the 21–23 : (1) adequate sample number for elastic staining, (2) adequate method for elastic staining, (3) assessment of cases without obvious elastic lamina, and (4) reproducibility as a prognostic factor.…”
mentioning
confidence: 99%